Comparative hepatoprotective effects of AMK and PAMK via Nrf2 signaling in broiler breeders - Lu, Baili; He, Jiayu; Pan, Shirou; Wei, Junhao; Li, Bingxin; Cao, Nan; Huang, Yunmao; Tian, Yunbo; Cheong, Ngai; Chen, Ying; Xu, Danning; Li, Wanyan (Frontiers in Veterinary Science, 2025)
Atractylodes macrocephala Koidz. (AMK) and its purified polysaccharide fraction (PAMK) are known for their antioxidant, anti-inflammatory, and hepatoprotective properties, showing potential benefits for poultry liver health. This study simulated hepatic oxidative stress in late-laying hens, a physiological stage characterized by increased metabolic demands and reactive oxygen species (ROS) generation, without exogenous hepatotoxic agents. Hens were randomly assigned to three groups: control (basal diet), AMK (basal diet + 15 g/kg AMK), and PAMK (basal diet + 400 mg/kg PAMK). Both AMK and PAMK significantly reduced serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) activities compared to control. Notably, PAMK showed superior efficacy, decreasing malondialdehyde (MDA) levels by 35.29% vs. 32.87% in AMK, and more effectively increasing antioxidant enzymes superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px). Histopathological analysis revealed better-preserved liver structure and less inflammatory infiltration in PAMK-fed hens. Mechanistically, both treatments upregulated Nrf2 and downstream antioxidant genes, with stronger activation observed in the PAMK group. In vitro, PAMK reduced H2O2-induced ROS accumulation and apoptosis in primary embryonic chicken hepatocytes, effects that were attenuated by the Nrf2 inhibitor ML385. In conclusion, PAMK exerts superior hepatoprotective effects compared to crude AMK by modulating the Nrf2 pathway, mitigating oxidative stress, apoptosis, and autophagy. Future research should evaluate PAMK's long-term safety, synergistic potential with other natural antioxidants, and cost-effectiveness in poultry production.